On the Performance of Web Services - Tari, Zahir; Phan, Ann Khoi Anh.; Jayasinghe, Malith; Abhaya, Vidura Gamini; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Performance of Web Services provides innovative techniques to improve the performance of Web Services, as well as QoS (Quality of Service) requirements. This includes Qos performance, reliability and security. The author presents two levels of Web Services: the (3z(Bkernel(3y (B(ithe SOAP engine which delivers messages from one point to another through various networks), and the (3z(Bserver side(3y (B(which processes heavy load / requests). The primary objective of this book is execution of applications delivered in a timely fashion. Case studies and examples are provided throughout this book.s
Introduction -- Background -- Benchmarking SOAP Bindings -- The Use of Similarity & Multicast Protocols to Improve Performance -- Network Traffic Optimisation -- Scheduling for Heavy Traffic -- Scheduling with Time Sharing -- Conclusion -- WSDL Specification for the Stock Quote Service -- SMP Message Schema -- A Sample SMP Message.
Keywords: Computer science; Operating systems (Computers).; Computer network architectures; Computer Communication Networks; Computer system performance; Computer Science; Performance and Reliability; Information Systems Applications (incl. Internet).; System Performance and Evaluation; Computer Applications; Computer Communication Networks; Computer Systems Organization and Communication Networks